UV Irradiated Graphene-Based Nanocomposites: Change in the Mechanical Properties by Local HarmoniX Atomic Force Microscopy Detection - Guadagno, Liberata (Materials (Basel), 2019)
Epoxy based coatings are susceptible to ultra violet (UV) damage and their durability can be significantly reduced in outdoor environments. This paper highlights a relevant property of graphene-based nanoparticles: Graphene Nanoplatelets (GNPs) incorporated in an epoxy-based free-standing film determine a strong decrease of the mechanical damages caused by UV irradiation. The effects of UV light on the morphology and mechanical properties of the solidified nanocharged epoxy films are investigated by Atomic Force Microscopy (AFM), in the acquisition mode “HarmoniX.” Nanometric-resolved maps of the mechanical properties of the multi-phase material evidence that the incorporation of low percentages, between 0.1% and 1.0% by weight, of graphene nanoplatelets (GNPs) in the polymeric film causes a relevant enhancement in the mechanical stability of the irradiated films. The beneficial effect progressively increases with increasing GNP percentage. The paper also highlights the potentiality of AFM microscopy, in the acquisition mode “HarmoniX” for studying multiphase polymeric systems.